Moens'written transmission of dalang lore - van Groenendael, Victoria M. Clara (UI Scholars Hub, 2016)
Much of the storytelling in Java is the profession of the puppeteers (dalang; also spelled dhalang) who perform and direct shadow theatre plays (wayang). They improvise their stories in the context which their performance requires. Unless commissioned to do so by a patron, it is very unusual for a dalang to sit down and actually write out a story (lakon). In the early decades of the twentieth century in the area of Yogyakarta, a kind of storytelling mini-industry arose at the instigation of some western scholarly patrons and laymen interested in Javanese popular culture. One such patron was Ir. J.L. Moens. He encouraged dalangs to write down folk tales and, as they were dalangs, they clothed these in the wayang idiom. After Moens' death in 1954, his unpublished collection of wayang stories was dispersed. In 1964 one part found its way into the Leiden University Library. The topics discussed are: how the Collectie Moens originated and what its purpose was; who its authors were; which tradition they acknowledged; and the relationship between the Collectie Moens and the court collections of Surakarta and Yogyakarta.